2014
DOI: 10.1080/17461391.2014.940558
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pedometer use on physical activity and body weight in obese women

Abstract: Physical activity and healthy eating are of the utmost importance in treatment of obesity. However obese generally tend to have a sedentary lifestyle. Walking is a form of physical activity that is both simple and can be performed by everyone, but it requires an objective measurement. Number of steps taken during tracking can be recorded with the pedometer, a device used to measure the level of physical activity. We aimed to investigate whether or not using pedometers as a motivational technique to increase th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 42 publications
1
20
0
2
Order By: Relevance
“…In addition, the beneficial effects of our intervention were not restricted by changes in body weight, but also extended to improvements in other aspects of body composition such as waist circumference. The current study recorded an overall reduction of -3.8% in waist circumference following the intervention, a finding that is consistent with previous pedometer-based studies that have shown significant reductions in waist circumference (Yu et al 2018;Cayir et al 2015;Chan et al 2004). It has become increasingly clear that waist circumference, a Fasting glucose (mmol/l) Responders 6.4 ± 1.4 5.7 ± 0.6 -10.9 0.008 Non-responders 6.0 ± 0.7 5.6 ± 0.5 -6.7…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the beneficial effects of our intervention were not restricted by changes in body weight, but also extended to improvements in other aspects of body composition such as waist circumference. The current study recorded an overall reduction of -3.8% in waist circumference following the intervention, a finding that is consistent with previous pedometer-based studies that have shown significant reductions in waist circumference (Yu et al 2018;Cayir et al 2015;Chan et al 2004). It has become increasingly clear that waist circumference, a Fasting glucose (mmol/l) Responders 6.4 ± 1.4 5.7 ± 0.6 -10.9 0.008 Non-responders 6.0 ± 0.7 5.6 ± 0.5 -6.7…”
Section: Discussionsupporting
confidence: 91%
“…2 Many comprehensive lifestyle intervention programs such as the Diabetes Prevention Program (DPP) 3 and behavior change strategies (alone or in combination) have been used to promote weight loss in obese, high-risk individuals with variable effects. These strategies include motivational interviewing, accountability/self-monitoring programs, food journals, 4-6 pedometers, 7,8 and mobile phone apps 9 for weight loss.…”
mentioning
confidence: 99%
“…In addition, pedometers are an inexpensive, effective tool for motivating physical activity (McCarthy & Grey, 2015). Setting and tracking step count goals using pedometers have been associated with weight loss among adults (Bravata et al, 2007; Cayir, Aslan, & Akturk, 2015; Richardson et al, 2008; Swift et al, 2012).…”
Section: Interventionmentioning
confidence: 99%